Getting too old for this : Population ageing and its economic consequences in Finland - Kotamäki, Mauri; Lehtimäki, Jonne (Elsevier, 2026)
Population ageing creates economic burden through shrinking labour forces and rising age-related expenditures, but existing literature provides only limited causal evidence on the magnitude of effects. This limits policymakers’ ability to prepare for demographic transitions. This paper studies Finland’s uniquely rapid demographic transition, where the old-age dependency ratio nearly doubled during 2010–2019, to identify causal effects of accelerated ageing. The paper uses the Synthetic Control Method and instrumental variable analysis to study the economic consequences of rapid ageing. Accelerated ageing operates through two channels: the contraction of the labour force reduces productive capacity while fiscal pressures increase due to pension and healthcare spending. Results show Finland’s rapid ageing reduced GDP per capita and productivity substantially over the decade, while general government debt increased significantly. These findings quantify the considerable costs of delayed demographic adaptation, demonstrating that the speed of ageing fundamentally determines economic outcomes and public finances in ageing societies worldwide.